Theoretical Analysis and Semianalytical Solutions for a Turbulent Buoyant Hydrogen-Air Jet - M. F. El-Amin; Shuyu Sun; Amgad Salama (Journal of Applied Mathematics)
Semianalytical solutions are developed for turbulent hydrogen-air plume. We derived analytical expressions for plume centerline variables (radius, velocity, and density deficit) in terms of a single universal function, called plume function. By combining the obtained analytical expressions of centerline variables with empirical Gaussian expressions of the mean variables, we obtain semianalytical expressions for mean quantities of hydrogen-air plume (velocity, density deficit, and mass fraction).